2022
DOI: 10.1111/jdv.18027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence and risk of acne in adolescent and adult patients with atopic dermatitis: a matched cohort study

Abstract: Background Use of Janus kinase 1 inhibitors in moderate‐to‐severe atopic dermatitis (AD) is associated with incident acne in adolescent and adults that is mostly mild, transient and treatable. There is a need for more knowledge about the risk and severity of acne in patients with AD. Objectives To examine the prevalence, incidence and risk of acne in adolescents and adults with AD using nationwide prescription data. Methods A matched cohort study of 6600 adults with AD and 66 000 controls was conducted using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…The mean age of patients with acne occurrence following JAK inhibitors was 29.6 years, with 37 being the oldest, which means that acne occurred within the age range of adult acne. This is in keeping with the results of Thyssen et al 2 who showed that the incidence of acne decreases with age, with the highest incidence rate per 1000 person-years in 18- to 29-year-olds; 11.2% and 9.2% in both the general population and population with AD, respectively. By contrast, the patients who participated in studies for RA and psoriatic arthritis, were aged >50 years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean age of patients with acne occurrence following JAK inhibitors was 29.6 years, with 37 being the oldest, which means that acne occurred within the age range of adult acne. This is in keeping with the results of Thyssen et al 2 who showed that the incidence of acne decreases with age, with the highest incidence rate per 1000 person-years in 18- to 29-year-olds; 11.2% and 9.2% in both the general population and population with AD, respectively. By contrast, the patients who participated in studies for RA and psoriatic arthritis, were aged >50 years.…”
Section: Discussionsupporting
confidence: 92%
“…14 Another possibility is that an immune slant toward T helper 1 and 17 after T helper 2 signaling inhibition may induce inflammatory lesions, and immune inhibition by JAK-1 inhibitors may play a pivotal role in the change of microbial colonization of the skin, including the colonization of Demodex folliculorum. 2 In contrast, there is a study showing the upregulation of JAK1 and JAK3 in acne skin lesions, which indicates that activation of the JAK signaling pathway is potentially related to acne pathophysiology, hinting at the possibility of therapeutic application of JAK inhibitors. 15 There is still marked heterogeneity in the interaction between the JAK pathway and acne eruption.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… Based on a matched cohort study, the incidence of acne is higher in adolescents with AD compared with adults with AD, but this difference was not apparent in patients receiving upadacitinib. Among adolescents in this report, all acne AEs were mild or moderate, with 1 patient discontinuing upadacitinib 30 mg due to moderate acne.…”
Section: Discussionmentioning
confidence: 99%
“…
The JEADV has recently published the article 'Incidence, prevalence and risk of acne in adolescent and adult patients with atopic dermatitisa matched cohort study' by Thyssen et al 1 In this article, the authors assessed the prevalence of acne vulgaris (acne)in patients with atopic dermatitis and treated with Janus kinase 1 (JAK1) inhibitors through an epidemiological study that was initiated upon results from several clinical trials in moderate-to-severe AD testing JAK 1 and JAK 2 inhibitors reporting cases of acne in patients having been treated with JAK inhibitors. These studies documented very high absolute numbers of acne cases in adolescents and adults, underlining the increased risk of acne in AD patients treated with JAK inhibitors.
…”
mentioning
confidence: 99%